Performance evaluation of mobile network operators in UiTM Perlis using data envelopment analysis / Nur Shafiqah Hamidon - Hamidon, Nur Shafiqah (2021)
Mobile network operators are a provider of services in terms of wireless communications to mobile users. In Malaysia, there are four main mobile network operators (MNO) subscribed by Malaysians, which are Maxis, Celcom, Digi, and U Mobile. However, the number of complaints from the customers continues to increase every year due to dissatisfaction with the services provided. Most of the customers face a difficult situation in choosing the most affordable MNO based on their preferences. The company of MNO also need to consider customer satisfaction to survive in the market and compete with the competitor. Quality of services, billing and price, customer services, network connectivity, and promotions and delighting customers are the major factors of customer satisfaction. A questionnaire was distributed to collect data from 265 mobile users through a simple random method. This study aims to measure the efficiency of the MNO and determine the ranking of the most preferred MNO based on customer satisfaction factors. In the Data Envelopment Analysis (DEA), the Slack-Based Measured (SBM) Model was used to calculate the efficiency of each operator, while Super SBM Model assisted in ranking the mobile network operators. The results of this study showed that Celcom is the most preferred mobile network operator and followed by U Mobile, Maxis, and Digi. Thus, the findings of this study can help mobile users choose the best mobile network operators, and telecommunication companies can also improve their service performance to satisfy their customers’ needs.